Characteristics, health care utilization and cost of patients hospitalized with heart failure - Winkler, Hanna; Riedlinger, Dorothee; Figura, Andrea; Schenk, Liane; Möckel, Martin; Reinhold, Thomas (Frontiers in Health Services, 2025)
BackgroundHospitalizations in patients with heart failure are common and their frequency increases with severity of disease. To provide optimal care to these high-risk patients, it is important to know their characteristics and health care utilization patterns.MethodsThis secondary data analysis of the EMANet data set used data from the hospital information system (HIS) of eight hospitals from the center of Berlin to identify patients with heart failure having had at least one hospital treatment during the year 2016. To evaluate the cumulative costs and associated health care utilization in patients with heart failure in 2016 HIS data was linked to individual health claims data from one statutory health insurance fund.ResultsWe analyzed health claims data from 970 patients with heart failure (43.4% female; mean age 74.4 years). The mortality rate per year was high at 23.9%. Total annual health care costs from the perspective of the statutory health insurance fund amounted to € 33,668 per patient in 2016. About 69% of total costs arose from hospital treatments. On average, patients spent 37 days in hospital. Ten days of these were caused by unplanned cardiovascular hospitalizations. The utilization of continuous outpatient care by a general practitioner or a cardiologist and a continuous prescription of guideline-based medication is associated with a reduction in the loss of lifetime due to hospitalizations or death.ConclusionsPatients hospitalized with heart failure have a high burden of morbidity and mortality, which results in a high level of health care costs. A large increase in health care costs and resource use relates to increasing severity of heart failure. Continuous outpatient care may reduce the burden of disease as well as health care costs.